„Pomoc nie tylko dla zgromadzenia mego…” Działalność edytorska benedyktynek wileńskich za rządów ksieni Franciszki Anny Wołłowiczówny - Gwioździk, Jolanta (Śląskie Studia Polonistyczne, 2017)
At the end of Saxon times and in the king Stanisław period, the Benedictine monastery in Vilnius was a community of people who used various types of prints; in accordance with the patterns of behavior and communication habits characteristic of the feminine contemplative community. The merits of Wołłowiczówna were twofold: she initialized the creation of the texts and she resumed and subsidized prints, which were published for the use of the monastery and to meet the religious needs of the society. The created texts were mainly works in the field of theology of spirituality, which certified the role of the written word in the monastery, and normative as well as formative works, which were used in the internal circulation of the monastery (and in other monasteries of various rules). The translated and native ascetical literature and brackish texts, however, were made available not only to the Benedictines, but also to the public. Also, occasional prints were published: those created and maintained the monastery’s bonds with the clergy and the local society and, at the same time, documented important events in the life of the community.